Endothelial Cell Adhesion Molecules- (un)Attainable Targets for Nanomedicines - Milošević, Nenad; Rütter, Marie; David, Ayelet (Frontiers in Medical Technology, 2022)
Endothelial cell adhesion molecules have long been proposed as promising targets in many pathologies. Despite promising preclinical data, several efforts to develop small molecule inhibitors or mAbs against cell adhesion molecules (CAMs) ended in clinical-stage failure. In parallel, many well-validated approaches for targeting CAMs with nanomedicine (NM) were reported over the years. A wide range of potential applications has been demonstrated in various preclinical studies, from drug delivery to the tumor vasculature, imaging of the inflamed endothelium, interfering with atherosclerotic growth or blocking immune cells infiltration. However, no NM drug candidate emerged further into clinical development. In this review, we will summarize the most advanced examples of CAM-targeted NMs and juxtapose them with known traditional drugs against CAMs, in an attempt to identify important translational hurdles. Most importantly, we will summarize the proposed strategies to enhance endothelial CAM targeting by NMs, in an attempt to offer a catalog of tools for further development.